Chronic hepatitis C infection — Noninvasive assessment of liver fibrosis in the era of direct acting antivirals. Issue 2 (February 2019) - Trivedi, Hirsh D.; Patwardhan, Vilas R.; Malik, Raza
Abstract: Significant advancements in the diagnosis and treatment of chronic hepatitis C infection and its associated fibrosis have revolutionized treatment of these patients over the last several years. Liver biopsy, the gold standard diagnostic method for evaluating liver fibrosis level, was routinely used prior to initiation of hepatitis C therapy, placing patients at an inherent risk of adverse events. The recent advent of noninvasive serologic and nonserologic measures of hepatic fibrosis level has reduced the need for liver biopsy significantly, thereby minimizing its associated risks. These noninvasive methods have been extensively studied in the era of interferon therapies and are increasingly recognized in the realm of direct acting antiviral agents as well. Their validation of use after having achieved a sustained virologic response is yet to occur, but the future remains promising. This review focuses on the various non-invasive diagnostic modalities of liver fibrosis and discusses how they can be applied to the care of patients undergoing direct acting antiviral therapy for hepatitis C. In the constantly evolving landscape of hepatitis C therapy, the review underscores the important prognostic value of fibrosis staging prior to HCV treatment and suggests potential uses for non-invasive fibrosis assessment following successful HCV eradication.